An effectiveness hierarchy of preventive interventions: neglected paradigm or self-evident truth?. (19th May 2017) - Capewell, Simon; Capewell, Ann
Abstract: Non-communicable disease prevention strategies usually target the four major risk factors of poor diet, tobacco, alcohol and physical inactivity. Yet, the most effective approaches remain disputed. However, increasing evidence supports the concept of an effectiveness hierarchy. Thus, 'downstream' preventive activities targeting individuals (such as 1:1 personal advice, health education, 'nudge' or primary prevention medications) consistently achieve a smaller population health impact than interventions aimed further 'upstream' (for instance, smoke-free legislation, alcohol minimum pricing or regulations eliminating dietary transfats). These comprehensive, policy-based interventions reach all parts of the population and do not depend on a sustained 'agentic' individual response. They thus tend to be more effective, more rapid, more equitable and also cost-saving. This effectiveness hierarchy is self-evident to many professionals working in public health. Previously neglected in the wider world, this effectiveness hierarchy now needs to be acknowledged by policy makers.